2009
DOI: 10.1007/s11431-009-0235-9
|View full text |Cite
|
Sign up to set email alerts
|

An estimation method on failure stress of micro thickness Cu film-substrate structure

Abstract: The failure of thin film-substrate structure occurs mainly at the thin film or the interface. However, the characterizing and estimating methods of failure stress in thin film are neither uniform nor effective because there are some complex effects of such as size, interface and stress state on the failure behavior of thin film-substrate structure. Based on the scanning electron microscope (SEM) in-situ investigation on the failure models of the Cu thin film-substrate structure and the nano scratched testing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…In addition, Asaro [ 109 ] and Wang et al . [ 39 ] independently reported how to estimate failure stress in thin films. For example, it is shown that when the free surface of thin film is unstable or thin enough the following relationship exists: where the subscript c denotes the critical mean.…”
Section: Evaluation Methods Of Interface Adhesion Strength and Failurementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Asaro [ 109 ] and Wang et al . [ 39 ] independently reported how to estimate failure stress in thin films. For example, it is shown that when the free surface of thin film is unstable or thin enough the following relationship exists: where the subscript c denotes the critical mean.…”
Section: Evaluation Methods Of Interface Adhesion Strength and Failurementioning
confidence: 99%
“…Wang et al . [ 25 , 35 , 39 , 78 , 92 , 93 ] used an electronic speckle pattern interferometry (ESPI) technology [ 94 , 95 ] and the digital image correlation (DIC) method [ 96 , 97 ], respectively, for measuring the deformation of highly flexible specimens of conducting polymer. Figure 7 shows a typical electronic speckle pattern interferometry system for measuring the in-plane displacement of a free surface by electronic speckle pattern interferometry (ESPI) technology.…”
Section: Microstructure-mechanical-conductive Properties Of Polymer Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the flexural stress was estimated using Eq. (7) from Wang et al (2009) and Eq. (8) from Yan and White (1999).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On the other hand, there are difficulties in mesh refinement using the FE method (Hutchinson and Suo, 1991;Fawcett, 1998;Yan and White, 1999;Michler and Blank, 2001;Zhao et al, 2002;Schwaiger and Kraft, 2003;Yang et al, 2014;Dean et al, 2015). Therefore, to investigate failure issues of thin coating layers/substrates, experimental study is the best and directly approach (Wang and Xu, 2003;2004;2009;Li et al, 2008a;2008b;Dean et al, 2015). In addition, it is necessary to estimate the delivery criterion of stress close to the interface of thin anodized coatings and thick substrates using SEM in-situ technology Wang and Fan, 2006;Jia et al, 2012;Ren et al, 2013;Ren and Wang, 2014).…”
Section: Introductionmentioning
confidence: 99%